Tubulointerstitial nephritis and uveitis (TINU) syndrome: a systematic review of its epidemiology, demographics and risk factors - Linda O. Okafor; Peter Hewins; Philip I. Murray; Alastair K. Denniston (Orphanet Journal of Rare Diseases, 2017)
Abstract Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare oculorenal inflammatory condition that was first described in 1975. In 2001 a major review identified 133 cases in the world literature and proposed key diagnostic criteria for the condition. Although acknowledged as rare, the limited data available prevented reliable estimates of the prevalence of the condition, and hampered elucidation of the relationship between genetic and environmental factors that contribute to its pathogenesis. In this review we have performed a systematic search on the epidemiology, demographics and proposed risk factors for TINU. Estimates of prevalence based on studies that explicitly report TINU cases suggest that it is diagnosed in 0.2–2% of patients attending specialist uveitis services, with variation reflecting a number of factors including level of diagnostic certainty required. The prevalence of uveitis in patients with tubulointerstitial nephritis (TIN) may be higher than currently recognised, particularly in the paediatric population. The prevalence of TINU is higher in younger age groups and there is a female preponderance although this gender effect appears weaker than suggested by early studies. Although important genetic contributions have been proposed, the small size of studies and variation between reports currently preclude identification of a ‘pro-TINU’ haplotype. Drugs and infections have been proposed as the leading acquired risk factors for the development of TINU; whilst the small size of TINU cohorts and issues of study design limit interpretation of many studies. Larger datasets from the renal literature suggest that the majority of these cases are precipitated by a drug-induced hypersensitivity reaction; however in many ophthalmic cases no clear precipitant is identified.